PERAN PEMERINTAH DALAM PEMBERDAYAAN MASYARAKAT DI BIDANG PERTANIAN DESA BULO WATTANG KECAMATAN PANCA RIJANG KEBUPATEN SIDENRENG RAPPANG - Muhammad Ilham Dubaili (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
This research aims to know how the role of village government in community empowerment in agriculture in the village of Bulo Wattang PancaRijang District Sidenreng Rappang and what factors influence the role of village government in community empowerment in the field of agriculture in the village Bulo Wattang Panca Rijang District Sidenreng Rappang. The data collection techniques that are done in this study are observations, interviews, Koesioner, and library studies. The Data is then analyzed using the frequency and percentage table. The population in this study was the farmers in the village of Bulo Wattang as much as 260, while a sample of a population of 72 farmers. Results of this research shows that the role of village government in the community empowerment in agriculture in the village Bulo Wattang Panca Rijang District Sidenreng Rappang with a cumulative result of 64% categorized as